IMAJI KEPAHLAWANAN DALAM SASTRA ANAK MUTIARA TANAH ARON KARYA I KETUT SANDIYASA - Ni Putu Ekatini Negari (LP3M Universitas PGRI Mahadewa Indonesia, 2020)
This paper aims at uncovering the images of heroism in the children literature of Mutiara Tanah Aron by I Ketut Sandiyasa. The data in this study were obtained through descriptions of behaviors and dialogues that show heroic values. It was also supported by environmental factors, such as the family environment, school environment, and rural natural environment. The characters’ behavior show love for the family, pets, and the natural environment that gives him life. This research is a qualitative research with the theory of semiotics, and assisted by reading and text analysis techniques. From the analysis result, it shows that the ability of thinking of an elementary school student to achieve his dream as a child who excels in the competition at the district level. This achievement can raise the name of the school and the name of the village where the historic monument was erected, namely the Tanah Aron Monument. The character can demonstrate his success through hard work, unyielding, and responsibility that is part of the values ​​of heroism, until finally the child gets the nickname Pearl of the Aron Land.